Microbiological Characterization of KPC-Producing Klebsiella Pneumoniae: A Systematic Review - Aiman Idrus Alatas; Delly Chipta Lestari (Journal of Community Health Provision, 2026)
Klebsiella pneumoniae (K. pneumoniae) is an opportunistic bacterium that causes nosocomial infections and usually affects people with malfunctioning immune systems. These bacteria can also cause potentially fatal community-acquired diseases. A high fatality rate has been documented in carbapenem-resistant K. pneumoniae, particularly carbapenemase-producing cases. This is due to few antibiotic therapy choices. This study aims to assess the microbiological characteristics of KPC-K. pneumoniae in terms of their genotypic features. This article reported a systematic review that used the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020 guidelines to identify articles related to carbapenem-resistant K. pneumoniae. Pubmed and SagePub, two online databases, were searched using pre-established inclusion and exclusion criteria. The search turned up six studies that showed K. pneumoniae contains numerous gene mutations that cause carbapenem resistance, including blaKPC, blaKPC-2, blaKPC-3, and blaKPC-23. The mutations in porins OmpK35, OmpK36, and OmpK37 also significantly contribute to this resistance. These findings indicated that the optimal combination of antibiotics should be tailored to the specific strain of K. pneumoniae with a carbapenem-resistant genotype, especially for KPC-Kp strains with a mutation in OmpK36. The findings of this systematic review offer vital information for creating successful strategies to fight carbapenem-resistant K. pneumoniae infections.